Preventive audiology An African perspective - Khoza-Shangase, Katijah (AOSIS, 2022)
This book is an original scholarly book that introduces the concept of preventive audiology, with a specific focus on the African context, which is in line with the South African re-engineered primary healthcare strategy as well as the World Health Organisation's approach. The book reflects on contextually relevant and responsive evidence-based perspectives, grounded in an African context on preventive audiology, in four major ear and hearing burdens of disease within the South African context: (1) early hearing detection and intervention, (2) middle ear pathologies, (3) ototoxicity, and (4) noise-induced hearing loss. The book represents innovative research, seen from both a South African and global perspective. It offers new discourse and argues for a paradigm shift in how audiology is theorised and performed, particularly in low-and-middle-income country contexts. The goal of this book is to motivate a paradigm shift in how the ear and hearing care is approached within this low-and-middle-income country context while arguing for Afrocentric best practice evidence that leads to next practice.